Effect of an educational intervention on parental readiness for premature infant discharge from the neonatal intensive care units. (1st October 2015) - Chen, Yongfeng; Zhang, Jun; Bai, Jinbing
Abstract: Aim: To examine the effect of an educational intervention on parental readiness for premature infant discharge from neonatal intensive care units. Background: Low readiness for discharge can result in negative healthcare outcomes for infants and their parents. However, few studies have examined the effect of discharge education programmes on parental readiness for premature infant discharge in Chinese critical care settings. Design: A quasi‐experimental study. Methods: Between October 2011–March 2012, 154 parents of premature infants were recruited from neonatal intensive care units of two tertiary hospitals in Central China. These parents were assigned to either the intervention or control group based on their entry order. Parents in the intervention group received two sessions of 60‐minute discharge education along with hospital routine care; parents in the control group only received hospital routine care. Parental readiness for discharge and quality of discharge education were assessed on the day of infant discharge from neonatal intensive care units. Independent samples t ‐test and linear regression were used to analyse the data. Results: Parental readiness for premature infant discharge was in the moderate level. Independent samples t ‐test showed that both mean scores of parental discharge readiness and discharge teaching quality from the intervention group were significantly higher than those in the control group. Linear regression analysis showed that discharge teaching quality explained 39·7% of the variance in parental readiness for premature infant discharge. Conclusion: Discharge education can improve parental readiness for premature infant discharge. Quality of discharge teaching can significantly predict parental readiness for premature infant discharge.